Mentoring and organizational support as predictors of internship satisfaction: the mediating role of grit among pre-service teachers - Cherryl C. Malonisio; Manuel O. Malonisio (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examined the influence of mentoring and organizational support on internship satisfaction among pre-service teachers, with grit as a mediating variable. Using a quantitative cross-sectional design, data were collected from 140 pre-service teacher interns and analyzed using partial least squares structural equation modeling (PLS-SEM). The results showed that mentoring and organizational support had significant positive effects on internship satisfaction. Grit also significantly predicted internship satisfaction and partially mediated the relationship between mentoring and internship satisfaction, while no mediation effect was found for organizational support. These findings highlight the central role of interpersonal mentoring in fostering perseverance and satisfaction during teaching internships. The study contributes to teacher education literature by clarifying how contextual support and personal perseverance interact to shape internship experiences in a developing-country context.